The Role of Learner-Focused Instruction in Teaching Arabic Phonemic and Phonological Awareness: Enhancing Language Acquisition and Proficiency (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study investigates the role of learner-focused instruction in teaching Arabic phonemic and phonological awareness with the aim of enhancing language acquisition and proficiency. Phonemic and phonological awareness play a crucial role in language learning, particularly in Arabic, where accurate pronunciation and phonetic skills are essential for effective communication. This research adopts a mixed-methods approach, combining quantitative data analysis and qualitative insights from Arabic language learners. The study examines the effectiveness of learner-focused instruction techniques, such as interactive activities, explicit instruction, and personalized feedback, in improving learners' phonemic and phonological awareness. The findings contribute to the existing body of research by highlighting the importance of incorporating learner-focused approaches into Arabic language instruction, promoting more accurate pronunciation, and enhancing overall language proficiency. The implications of this study can inform language educators and curriculum designers in developing effective teaching strategies to support Arabic language learners' phonemic and phonological development.